Molecular Mechanism of Response and Adaptation of Antioxidant Enzyme System to Salt Stress in Leaves of Gymnocarpos przewalskii - Jianwei Qi; Yongzhong Luo; Haixia Huang; Songsong Lu; Fei Zhao; Zhuo Deng; Yingde Qiu (Plants, 2023)
The antioxidant enzyme system is the main defense system responsible for maintaining cellular reactive oxygen species (ROS) homeostasis and normal plant growth and development after saline stress. In this study, we identified and characterized the members of the SOD, APX and CAT gene families of the antioxidant enzyme system in Gymnocarpos przewalskii, using plant physiology and molecular biology methods, and analyzed the pattern of enzyme activity in response to NaCl stress. It was found that seven, six and two genes of SOD, APX and CAT gene families, respectively, were expressed in the leaf tissue of G. przewalskii, in which most of the genes were significantly upregulated under NaCl stress, and the enzymatic activities were in accordance with the gene expression. Three positive selection sites in the GpCAT1 gene can increase the hydrophilicity of the GpCAT1 protein, increase the volume of the active site and increase the affinity for H2O2, thus improving the catalytic efficiency of GpCAT1. The results of the present study provide new insights for further investigations of the evolution and function of the SOD, APX and CAT gene families in G. przewalskii and their essential roles under salt stress, and the findings will be useful for revealing the molecular mechanism of salt tolerance and breeding of salt-tolerant plants.